Factors Affecting Corrosion in Gulf of Finland Brackish Water - Jari Aromaa; Olof Forsén (International Journal of Electrochemistry)
The Baltic Sea is a relatively shallow inland sea surrounded by the countries of North-Eastern Europe and Scandinavia. The brackish water in the Baltic Sea has low salt concentration and it is typically one-sixth of the ocean seawater. The “nominal” amount of dissolved solids, upon which formulae for artificial seawater are based, is about 34,500 ppm, of which most is sodium chloride. The major constituents are those whose concentrations are greater than 1 mg/L and are not greatly affected by biological processes. The ratio of concentrations of these ions and molecules to each other is relatively constant. Corrosion rates were determined in long-term tests in Gulf of Finland brackish water off Helsinki. The water temperature varies through the year from about 0°C in January to 15-16°C in June to August. Salinity is 4–6‰, highest at the end of summer and lowest when ice melts. pH is between 7.0 and 8.1. Weight loss tests from one- to four-year tests for steel, stainless steel, copper, aluminium, zinc, and galvanized steel are reported and compared to short term laboratory tests in artificial seawater. Tests for passivation rates and crevice corrosion for stainless steel are discussed in terms of environment variation. The effect of corrosion on strength of steel is also discussed.